DEVELOPMENT OF CROSSWORD PUZZLES TO IMPROVE COOPERATIVE CHARACTER IN THE SUBJECT OF PANCASILA EDUCATION FOR SECOND GRADE ELEMENTARY SCHOOL STUDENTS - Ady Alawy, Gymnastiar; Sunaryati, Titin (Journal Of Educational Experts (JEE), 2026)
This study was motivated by the lack of variety in the learning media used by teachers, which has resulted in low levels of cooperation among students in their daily lives. The aim of this study is to develop crossword puzzle learning media to enhance students' cooperative behavior in the subject of Pancasila Education. This study employs the research and development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The results of the study indicate that 1) crossword puzzles are highly suitable for use, as evidenced by the results of the subject matter expert assessment (65.3%), language expert assessment (84%), and media expert assessment (97.3%); 2) crossword puzzles are practical and engaging for use in learning, as evidenced by the results of the teacher and student response assessment, which yielded an average score of of 92.25% (3) crossword puzzles are effective in improving students' cooperative character, as evidenced by the results of the cooperative character questionnaire, which obtained a score of 93% in the very effective category.